Procuring Infrastructure Public-Private Partnerships Report 2018 : Assessing Government Capability to Prepare, Procure, and Manage PPPs - World Bank (World Bank, Washington, DC, 2018)
Procuring Infrastructure PPPs 2018 assesses the regulatory frameworks and recognized good practices that govern PPP procurement across 135 economies, with the aim of helping countries improve the governance and quality of PPP projects. It also helps fill the private sector’s need for high-quality information to become a partner in a PPP project and finance infrastructure. Procuring Infrastructure PPPs 2018 builds on the success of the previous edition, Benchmarking PPP Procurement 2017, refining the methodology and scope based on guidance from experts around the world, as well as expanding its geographical coverage.